Meaningful Work, Kepemimpinan Transformasional dan Komitmen Organisasi Guru - Wahyuni, Sri; Suroso, Suroso; Farid, Muhammad (Faculty of Psychology, Universitas 17 Agustus 1945 Surabaya, 2019)
This study aims to explore the relationship between meaningful work, transformational leadership and organizational commitment of teachers both simultaneously and also partially. The subjects in this study were SDIT Ghilmani teachers who had 1 year minimum service period. Data analysis techniques using multiple regression analysis with the help of SPSS Versiaon 20. The results of the study stated that there is a relationship between meaningful work, transformational leadership and organizational commitment in SDIT Ghilmani Surabaya teachers, so that both of these variables can predict organizational commitment. The results of the study stated that there is a relationship between meaningful work, transformational leadership and organizational commitment in SDIT Ghilmani Surabaya teachers, so that both of these variables can predict organizational commitment. There is a partial positive relationship between meaningful work with organizational commitment and there is no positive relationship partially bertween transformational leadership and organizational commitment.